2007
DOI: 10.1038/sj.leu.2404602
|View full text |Cite
|
Sign up to set email alerts
|

Significant impact of survivin on myeloma cell growth

Abstract: Survivin is a fascinating member of the inhibitor of apoptosis protein (IAP) family with its dual roles in mitosis and apoptosis, and emerges as an attractive target for cancer therapy. Multiple myeloma (MM) is a plasma cell malignancy, characterized by deregulated proliferation, cell-death processes and fatal outcome. We thus investigated survivin expression in myeloma cells and its role in MM biology to evaluate its potential interest as a target in MM treatment. Our results describe the cancerspecific overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 40 publications
4
46
0
3
Order By: Relevance
“…The decrease in survivin expression, which was not appreciated at RNA level, was likely a consequence of PI3K/AKT pathway inhibition, as previously shown by specific AKT inhibition in the MM cell context [32]. Notably, modulation of Mcl-1 and survivin, as well as AKT, may have therapeutic relevance in this disease [25,47,49]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 M a n u s c r i p …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The decrease in survivin expression, which was not appreciated at RNA level, was likely a consequence of PI3K/AKT pathway inhibition, as previously shown by specific AKT inhibition in the MM cell context [32]. Notably, modulation of Mcl-1 and survivin, as well as AKT, may have therapeutic relevance in this disease [25,47,49]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 M a n u s c r i p …”
Section: Discussionmentioning
confidence: 62%
“…3B), known as survival factors in myeloma cells [9,25]. Expression levels of Bcl-2 were not affected by drug treatment (not shown).…”
Section: Apoptosis Inductionmentioning
confidence: 89%
“…We found that echinomycin or siRNA against HIF-1α specifically blocked both basal and IGF-1-induced survivin levels. Survivin is widely expressed in many types of established myeloma cell lines and contributes to cell survival (28,44). Romagnoli et al (44) showed that siRNA-mediated inhibition of survivin expression sensitizes myeloma cells to conventional antimyeloma agents, including melphalan.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is widely expressed in many types of established myeloma cell lines and contributes to cell survival (28,44). Romagnoli et al (44) showed that siRNA-mediated inhibition of survivin expression sensitizes myeloma cells to conventional antimyeloma agents, including melphalan. Furthermore, Peng et al found that HIF-1 regulates survivin expression in breast cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…mDC ZA+ were very effective in both CTRL and MM NR, and resulted in the proliferative expansion of but also in those NR MM in which gd T cell proliferation was reinstated. SRV was selected as a prototypic tumor-associated Ag because it is expressed by myeloma cells and contributes to their survival (38). SRV-specific T cells have been tolerized but not deleted from the MM T cell repertoire (23), and their effector functions can be reinstated by appropriate SRV presentation and T cell stimulation (39,40).…”
Section: Antagonism Of Za and Gd T Cells Versus Tregsmentioning
confidence: 99%